(untitled) (Chemical Engineering Research Bulletin, 2010)
In this study different brands of Ordinary Portland Cement (OPC) produced and available in Khyber Pakhtoon Khwa, Pakistan have been studied for different chemical parameters and compared with British standard specifications. The amounts of chemical constituents like SiO2, Al2O3, Fe2O3, CaO, MgO, SO3, insoluble residue (IR), free lime and loss on ignition (LOI) were determined in accordance with British Standard (BS) Specifications. All the results are presented to provide both quantitative and qualitative notion of several locally produced ordinary Compositions of most of this constituents as determined experimentally were within the range of the standard values. The possible reasons for variation in chemical compositions and their consequences have been discussed. Keywords: Ordinary Portland cement, Chemical Composition, Quality Verification DOI = 10.3329/cerb.v14i1.4320 Chemical Engineering Research Bulletin 14 (2010) 45-49